Students’ errors in solving mathematical problems - Dwita, Asri; Retnawati, Heri (AIP conference proceedings, 2022)
Education is an important aspect so that success in education needs to be achieved by every single country in the world. Success in education can be seen from the results of assessments conducted on several subjects, one of them is mathematics. Based on PISA and TIMSS, Indonesian mathematics performance is still in the low rate. It means that many things need to be evaluated. This literature review examines students’ errors in answering mathematical problems. This is for teacher’s guidance in assessing student’s answers so that teachers can evaluate the existing learning. 10 articles from various accredited journals reviewed in this article. The results show that 15 students’ errors can be found in solving mathematical problems.